Effective or harmful: evaluation of locally applied antibiotics on adipose tissue during lipofilling to the breast ; an in vitro study - Diehm, Yannick; Gazyakan, Emre; Wang, Yiping; Siegwart, Laura C.; Haug, Valentin; Kotsougiani-Fischer, Dimitra; Kneser, Ulrich; Fischer, Sebastian (International journal of molecular sciences, 2023)
Lipofilling is a frequently used and safe procedure for breast reconstruction. One of the most feared complications is soft tissue infection following lipofilling. Because of this, some surgeons propose the practice of rinsing fat grafts with antibiotics. This study investigates the effect of antibiotic rinses on fat grafts in an in vitro model. Adipocytes and stem cells were isolated from fat tissue harvested during 24 lipofilling procedures and incubated with different doses of clindamycin or cefazolin. Cell viability, metabolism, proliferation, and differentiation capacities were analyzed by gross morphology, fluorescence staining, -(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromid (MTT-), and Glyceraldehyde 3 Phosphate Dehydrogenase (G3PD)-assay as well as reactive oxygen species (ROS)-assay. Cefazolin and clindamycin led to significant reduction of cell viability of adipocytes. High doses of both antibiotics led to a rupture of adipocytes with visible free lipid droplets. Cell metabolism was significantly decreased after incubation with both antibiotics. There was a significant increase in ROS production. Exposure to clindamycin and cefazolin led to morphological changes in stem cells in a dose- and time-dependent manner. Furthermore, differentiation potential was significantly reduced. Antibiotic susceptibility testing, however, showed that low concentrations of antibiotics effectively inhibited bacterial growth in contaminated fat grafts. This study confirms that rinsing fat grafts with clindamycin or cefazolin not only overly prevents infection but also has cytotoxic and metabolic effects on adipocytes. Therefore, based on these results, the routine clinical application in high doses cannot be recommended.
Gesehen am 27.03.2023